Justice, Land, and Sharia: Conceptualizing Agrarian Courts in the Settlement of Land Ownership Disputes - Tambunan, Rico J.R.; Safa'at, Rachmat; Permadi, Iwan; Sulistyarini, Rachmi (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2025)
Agrarian disputes remain pervasive and complex, frequently involving violations of land rights, land grabbing, and overlapping claims. Such disputes often span civil, administrative, and even criminal dimensions, resulting in fragmented litigation before the General Courts and the State Administrative Courts. This fragmented adjudication has produced inconsistent and conflicting judicial decisions, thereby undermining legal certainty and justice in the land sector. These conditions underscore the urgency of establishing a specialized agrarian court with a clear institutional and procedural framework. This study aims to formulate a conceptual model of an agrarian court and to propose its future institutional mechanism in order to ensure legal certainty in the resolution of agrarian disputes. From the perspective of Islamic law, land ownership constitutes a protected right (ḥifẓ al-māl) that necessitates an effective and just dispute-resolution mechanism. This research employs a normative legal methodology using statutory, case, comparative, and conceptual approaches, supported by primary, secondary, and non-legal materials. The findings propose the Agrarian Court Concept based on the “3Ps” framework—Position, Procedure, and Professionalism—which emphasizes institutional clarity, specialized procedural rules, and competent adjudicators. This model is designed to prevent future disputes, harmonize judicial decisions, and resolve agrarian conflicts in a manner that promotes legal certainty, justice, and the broader objectives of law, including the principle of enjoining good and preventing harm.